Hydrogeology and origin of waters of the Panyam Volcanic Line springs, Jos Plateau, Nigeria - B., Longpia C. (Vietnam Journal of Earth Sciences, 2021)
The PVL springs are used for both domestic and agricultural purposes. The seepage from the springs has resulted in producing a large expanse of wetlands and is therefore intensively use for dry season farming. The aim of this study was to determine the hydrogeological, hydrochemical characteristics, origin and their suitability for domestic and irrigation. The hydrogeology of the springs was determined by field mapping. The physico-chemical parameters were determined in the field and by laboratory methods. For the cation and anion analysis the ICP-MS and the wet methods were employed respectively. The stable isotope composition of oxygen (δ18O) and hydrogen (δ2H) were analyzed by Isotope Ratio Mass Spectrometer. The hydrochemical analysis revealed that the PVL springs waters are generally neutral with an average pH value of 7.3. The average TDS and EC values are 127.8mg/l and 246µs/cm respectively. These values fall within fresh water class. The average Mg2+,Ca2+, Na+ and K+ cation concentration values are 16.3mg/l, 15.8mg/l, 10.8mg/l and 5.58mg/l respectively. The average anions concentration of HCO3-, SO4 and Cl- are 140mg/l, 8.6mg/l and 3.4mg/l respectively. Piper trilinear diagram show that the spring waters is predominantly Mg-Ca-HCO3 water type with potable qualities based on WHO drinking water standards. The sodium Adsorption Ratio (SAR) and Sodium Soluble Percentage (SSP) values range between 0.44 to 0.84 and 26.4 to 54% respectively and falls within irrigation quality standards. Stable isotope compositions of δ18O and δ2H ranges from -3.60/00 to -4.90/00 and -200/00 to -280/00 respectively falls within the meteoric water composition. This is further affirmed by the δ2H versus δ18O plot on the correlation diagram with Standard Meteoric Water Line.